Design and Development of Object Detection Radar with IoT-Based Matlab Software Visualization - Ihsan, Dias Khairul Ihsan; Fadlilah, Umi; Kusban, Muhammad (Universitas Muhammadiyah Surakarta, 2024)
Radar is an abbreviation for Radio Detection and Ranging, which means an electromagnetic wave system that functions to detect, measure and map objects in the surroundings. So far, the development of radar technology has tended to focus on object detection without considering effective integration and connectivity. Therefore, this research aims to develop a radar that can detect, measure and differentiate between moving and stationary objects. This research does not only pay attention to the detection aspect, but also integrates Matlab R2022a for visualization, Internet of Things (IoT) for centralized connectivity and the Blynk mobile application to increase the efficiency of object monitoring. This research uses ultrasonic sensors and Passive Infra-Red (PIR) sensors, ultrasonic sensors to read distance parameters and PIR sensors to detect moving or stationary objects. The ultrasonic and PIR sensors will be controlled by the ESP32 and serve as a centralized connectivity system that will connect to a Web server and mobile devices, while the Matlab R2022a software will visualize the environment around the radar at a 180o angle and connect with Thingspeak and the PushBullet mobile application. The results of the test are compared with a standard measuring instrument, namely a meter. In this research analysis, error calculations are used to see the uncertainty value of the sensor readings used. Based on research, the ultrasonic sensor reading accuracy results were 98.99% and for the PIR sensor the sensor could read every test angle starting from 30, 60, 90 120 and 150 degree, however at angles 30 and 150 degree it had quite a long delay.